Analysis of Public Response to The Use of Chemical Castration for Sexual Offenders in Indonesia - Khairina Hanum Hasibuan, Anggi; Priyo Agus Santoso, Aris; Aryono, Aryono (PT. Publikasiku Academic Solution, 2024)
Sexual violence includes various immoral behaviors such as sexual insults, touching unauthorized body parts, viewing and sending unwanted sexual and pornographic images, forced participation in sexual and pornographic activities, rape, sexual torture, female genital mutilation, sexual exploitation, sexual slavery, forced prostitution, forced pregnancy, forced sterilization, forced abortion, and intentional infection with sexually transmitted diseases such as AIDS. Sexual crimes also occur in a state of war, mainly as a tool to oppress a country. In Indonesia, Law no. 17 of 2020 lists chemical castration as one of the solutions in preventing repeat sexual crimes for children. Chemical castration is one of the sanctions that is condemned by the world community but has a major impact in reducing the rate of sexual crime cases. This study aims to analyze the results of the response received by the community to the existence of chemical castration punishment in sexual offenders. The research method in this study uses the type of empirical research and the nature of qualitative research, with data collection methods in the form of questionnaires and secondary data from interviews from youtube and other written documents. The results of this study. Of the 100 respondents who agreed to the existence of chemical castration by answering yes and strongly agreeing, reaching 60%. Doubts about the success of the implementation of chemical castration can have a deterrent effect on sexual offenders. However, most people agree that the existence of chemical castration needs to be carried out not only pedophilia but also perpetrators of sexual crimes against women).